Logistics and the Circular Economy - Tavares, Fernando Oliveira (2024)
There is a strong interconnection between logistics and the circular economy, with emphasises on how the two are intertwined in the quest for efficient resource management and sustainability. The circular economy proposes replacing the traditional linear model, prioritizing the reduction, reuse, recovery and recycling of materials and products. Logistics plays a critical role in waste management, material recovery, sustainable design, energy efficiency and resource sharing. Thus, logistics is fundamental to the effective functioning of the circular economy, and digitalisation is an essential way of making logistics more efficient in the circular economy; and overcoming the challenges such as the lack of coordination in the supply chain need to be overcome. Logistics is an essential part of the successful transition to the circular economy, making business processes more sustainable and environmentally friendly.